2001
DOI: 10.1074/jbc.m107831200
|View full text |Cite
|
Sign up to set email alerts
|

NFκB Activation Is Required for the Neuroprotective Effects of Pigment Epithelium-derived Factor (PEDF) on Cerebellar Granule Neurons

Abstract: Pigment epithelium-derived factor (PEDF) protects immature cerebellar granule cells (1-3 days in vitro)against induced apoptosis and mature cells (5؉ days in vitro) against glutamate toxicity, but its precise mechanism is still unknown. Because the transcription factor NFB blocks cell death, including neuronal apoptosis, we have investigated the ability of PEDF to exert its effects via NFB activation. PEDF induced an increased phosphorylation of IB␣, decreased levels of IB proteins, and translocation of p65 (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
2
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 63 publications
3
81
2
3
Order By: Relevance
“…Inhibition of NF-kB nuclear translocation by PEDF would thus suppress subsequent NF-kB DNA binding and activation. Interestingly, previous studies showed that activation of NF-kB in neurons is responsible for the neuroprotective activity of PEDF (Yabe et al 2001). In our present study, we did not observe a protective effect of PEDF on HOG-LDL-induced apoptosis of pericytes nor activation of NF-kB by PEDF (data not shown), suggesting that the effect of PEDF on NF-kB activation is cell-type specific.…”
Section: Discussioncontrasting
confidence: 45%
“…Inhibition of NF-kB nuclear translocation by PEDF would thus suppress subsequent NF-kB DNA binding and activation. Interestingly, previous studies showed that activation of NF-kB in neurons is responsible for the neuroprotective activity of PEDF (Yabe et al 2001). In our present study, we did not observe a protective effect of PEDF on HOG-LDL-induced apoptosis of pericytes nor activation of NF-kB by PEDF (data not shown), suggesting that the effect of PEDF on NF-kB activation is cell-type specific.…”
Section: Discussioncontrasting
confidence: 45%
“…A differential role of TNFR1 and TNFR2 has also been reported for hippocampal neurons responding to TNF alone with TNFR1 inducing both NF-B activation and cell death, whereas TNFR2 was found to stimulate p38 mitogen-activated protein kinase (11). However, this study neither addressed the functional significance of TNFR2-mediated p38 activation nor resolved the underlying mechanism of apoptosis dominance in these cells in the presence of an apparently strong NF-B activation (11), which is considered to play an important role in neuroprotection (34). As an example, the (35,36).…”
Section: Tnfr1contrasting
confidence: 41%
“…One potential mediator of MEK-ERK-independent B-Raf signaling is NF-jB. Several studies performed in a variety of in vivo and in vitro paradigms have shown the importance of NF-jB for neuronal survival (Yu et al 1999;Glazner et al 2000;Koulich et al 2001;Yabe et al 2001;Bhakar et al 2002;reviewed in Mattson et al 2000). The ability of c-Raf to signal via NF-jB in a MEK-ERK independent manner has been documented (Baumann et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-jB protects neurons against a variety of apoptotic stimuli and reduced NF-jB activity has been associated with neurodegeneration both in vitro and in vivo survival (Yu et al 1999;Glazner et al 2000;Koulich et al 2001;Yabe et al 2001;Bhakar et al 2002;reviewed in Mattson et al 2000). Although the precise mechanism has not been elucidated, c-Raf is known to activate NF-jB in non-neuronal cells via a MEK-ERKindependent mechanism (Foo and Nolan 1999;Pearson et al 2000).…”
Section: Gw5074 Delays Down-regulation Of Akt Activity But Inhibits Amentioning
confidence: 99%